Association of serum calcium, vitamin D, and C-reactive protein with all-cause and cause-specific mortality in an osteoarthritis population in the UK: a prospective cohort study - Kai Fu; Qianying Cai; Xinzhong Jin; Lingxiao Chen; Win Min Oo; Vicky Duong; Guangyi Li; Zhaohua Zhu; Changhai Ding; Changqing Zhang; Youshui Gao; David J. Hunter (BMC, 2024)
Abstract Background Osteoarthritis is a prevalent musculoskeletal condition, but the role of specific serum biomarkers, such as calcium, vitamin D, and C-reactive protein (CRP), in predicting mortality among individuals with osteoarthritis remains unclear. Methods This observational study analyzed longitudinal data from over 500,000 participants in the UK Biobank, identifying those with osteoarthritis using ICD-9/10 codes or self-reported history. We performed multivariable cox-regression and flexible parametric survival model (FPSM) for survival analysis, with adjustments made through the inverse probability of treatment weight (IPTW) for baseline covariates identified by directed acyclic graphs (DAGs). Results Of the 49,082 osteoarthritis population, the average age was 60.69 years, with 58.7% being female. During the follow-up period exceeding 15 years, a total of 5,522 people with osteoarthritis died. High serum calcium levels, compared to normal serum calcium levels, were significantly associated with all-cause mortality (hazard ratio (HR) 1.33, 95% confidence interval (CI) 1.11, 1.59), cardiovascular diseases (CVD)-related deaths (HR 1.55, 95% CI 1.05, 2.29), and other deaths (HR 1.59, 95% CI 1.20, 2.11). Low serum calcium levels, compared to normal serum calcium levels, was linked with CVD-related deaths (HR 2.06, 95% CI 1.02, 4.14). Vitamin D insufficiency, compared to sufficient vitamin D levels, was correlated with all-cause mortality (HR 1.22, 95% CI 1.13, 1.33), CVD-related deaths (HR 1.43, 95% CI 1.20, 1.72), and other deaths (HR 1.26, 95% CI 1.09, 1.45) but not with cancer-related deaths. High serum CRP levels, compared to normal CRP levels, were associated with all outcomes (all-cause mortality: HR 1.22, 95% CI 1.12, 1.33; CVD-related death: HR 1.24, 95%CI 1.03, 1.49; cancer-related death: HR 1.23, 95% CI 1.09, 1.40; other deaths: HR 1.19, 95%CI 1.03, 1.38). Conclusions Both high and low serum calcium levels, elevated CRP, and vitamin D insufficiency are potential predictors of increased mortality risk in the osteoarthritis population. These findings emphasize the importance of monitoring and possibly addressing these serum biomarkers in osteoarthritis populations to improve long-term outcomes. Further studies are needed to understand the underlying mechanisms and to propose therapeutic interventions.